2021
DOI: 10.3389/fcomm.2021.660917
|View full text |Cite|
|
Sign up to set email alerts
|

When the Easy Becomes Difficult: Factors Affecting the Acquisition of the English /iː/-/ɪ/ Contrast

Abstract: The degree of similarity between the sounds of a speaker’s first and second language (L1 and L2) is believed to determine the likelihood of accurate perception and production of the L2 sounds. This paper explores the relationship between cross-linguistic similarity and the perception and production of a subset of English vowels, including the highly productive /iː/-/ɪ/ contrast (as in “beat” vs. “bit”), by a group of Spanish/Catalan native speakers learning English as an L2. The learners’ ability to identify, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Remember that none of the proposed predictors of Mandarin equivalence classification foresaw that the Russian prevoiced stops and short-lag stops would be equated with the Mandarin short-lag stops. Indeed, recent work (Cebrian et al, 2021; Munro, 2021) has shown how the construct of phonetic similarity (more aptly what I would call E-similarity) is not a straightforward predictor of individual performance within an L1 grouping. Rather, the empirical results need to be contextualized by considering such factors as cue re-weighting as part of the learning theory which maps intake onto phonological representations.…”
Section: Discussionmentioning
confidence: 99%
“…Remember that none of the proposed predictors of Mandarin equivalence classification foresaw that the Russian prevoiced stops and short-lag stops would be equated with the Mandarin short-lag stops. Indeed, recent work (Cebrian et al, 2021; Munro, 2021) has shown how the construct of phonetic similarity (more aptly what I would call E-similarity) is not a straightforward predictor of individual performance within an L1 grouping. Rather, the empirical results need to be contextualized by considering such factors as cue re-weighting as part of the learning theory which maps intake onto phonological representations.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches regarding foreign accents and transfers have focused on and investigated segmental production (Cebrian, Gorba, & Gavaldà, 2021). Stress, intonation, and rhythm are examples of prosodic qualities that receive less research attention than segmental features, even though prosodic features have been proven to contribute more to how clear they are understood and considered to be how different and strange their intonation as detailed (Widya & The Profile of Short Vowel 'A'.... (Rike Febriyanti) Agustiana, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the assessment of segmental production–a focus of the present study–the elicitation task must yield enough usable exemplars of the target sound to allow satisfactory analysis. Possible tasks include simple repetition (Flege and Eefting, 1988 ), reading aloud, delayed repetition, in which the speaker reformulates an utterance with a target item (Flege et al, 1995 , 1999 ; Munro and Derwing, 2008 ), picture naming (Flege and Davidian, 1984 ; Cebrian et al, 2021 ), or less-constrained tasks, such as timed picture descriptions (TPD), in which speakers are instructed to use particular target items while giving their descriptions (Saito and Munro, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…That focus is appropriate because differences in the two languages' vowel inventories appear to underpin known difficulties for Cantonese speakers (Meng et al, 2007;Wong, 2015). Also, as observed by Cebrian et al (2021), the English high vowel contrast between /i/ and /I/ has been the subject of much interest in L2 phonetics research, first because it has a high functional load in English, distinguishing many pairs of common words such as heat and hit (Levis and Cortes, 2008;Sewell, 2017). Second, it poses perceptual and productive difficulties for speakers from diverse L1 backgrounds, including Catalan, Mandarin, Russian, and Spanish (Mora and Fullana, 2007;Kondaurova and Francis, 2008;Munro and Derwing, 2008).…”
Section: Introductionmentioning
confidence: 99%